Emerging Technology and Crisis Management in The Halal Industry Issues and Recent Developments - Rahman, Nor Aida Abdul; Ali, Mohd Helmi (Springer Nature Singapore : Imprint: Springer, 2024)
XVI, 297 p. 22 illus., 16 illus. in color.